Synergism between immune activators and progestogens: differential effects on gene expression and HIV-1 replication and the role of the glucocorticoid receptor - Moliki, Johnson Mosoko (Department of Molecular and Cell Biology, 2019)
Globally, women account for more than half of the 36.9 million people living with HIV-1. In some regions particularly Sub-Saharan Africa, women of child-bearing age are at great risk of being infected with HIV-1 than men of the same age group. Transmission is mainly through penetrative vaginal intercourse with an infected male partner. Current evidence suggests that women using certain types of progestin-only hormonal contraceptive methods have a higher risk of HIV-1 infection. In addition, there is evidence suggesting that genital tract infections (GTIs), which have high prevalence in SubSaharan Africa, also modify the risk of HIV-1 infection in women. Incidentally, regions were progestogen-only hormonal contraceptives use and genital tract infections are prevalent also have with high rates of HIV-1 prevalence in women. This raises the question whether medroxyprogesterone acetate (MPA), norethisterone enanthate (NET) or levonorgestrel (LNG), the active compounds in progestogen-only hormonal contraceptives, cooperate with inflammation associated with GTIs to further elevate the risk of HIV-1 acquisition in women. Current evidence suggests MPA, LNG and NET differentially the expression of immune function genes relevant for HIV-1 infection in the female genital tract (FGT). In addition, there is evidence suggest that MPA and LNG impairs the integrity of mucosal barrier of the FGT. This study investigated the central hypothesis that MPA, NET and LNG acting alone or in synergy with immune activators [tumour necrosis factor-alpha (TNF) and lipopolysaccharide (LPS)] via the glucocorticoid receptor (GR) regulate the expression of genes of relevant for maintaining the integrity of genital tract mucosal surfaces, mucosal permeability, select immune function genes and HIV-1 replication. This hypothesis was investigated in the endocervical epithelial End1/E6E7 cell, ectocervical tissues explants from pre-menopausal women, primary genital tract epithelial cells, peripheral blood mononuclear cells (PBMCs) and the TZM-bl indicator cell line. Gene expression analysis in responses to progestogen alone or in combination with immune activators was performed by real-time PCR, ELISA, Luminex assays and western blotting. The role of the GR was investigated using RU486 or GR siRNA knockdown. Mucosal barrier integrity and permeability was assessed by confocal microscopy and transepithelial electrical resistance measurements. For infection assays, TZM-bl cells were exposed to HIV-1Bal-Rellina infectious molecular clones (IMCs) before treatment progestogen alone or in combination with immune activators. In addition, TZM-bl cells were preconditioned with supernatants from PBCs treated alone with progestogen or in combination with immune activators before exposed to HIV-1Bal-Rellina IMCs. In the absence of TNF, MPA at physiologically relevant doses acted via the GR to downregulate claudin-4 mRNA expression in End1/E6E7 cells, with MPA behaving like a partial GR agonist when compared to dexamethasone (DEX). Similarly, MPA acted via the GR to selectively upregulate CCL20 mRNA expression in End1/E6E7 cells, with MPA behaving like a full GR agonist when compared to hydrocortisone (CORT). It was also observed that MPA upregulated toll-like receptor (TLR)2 mRNA expression, but reduced interleukin (IL)6 and IL1β mRNA expression in End1/E6E7 cells. Neither NET not LNG regulated claudin-4 and immune function expression in End1/E6E7 cells. The addition of TNF, on the other hand, did not alter the effect of MPA on claudin-4 expression, suggesting that there is no cooperativity between MPA and TNF in regulating this gene. Neither NET nor LNG was found to cooperate with TNF to regulate claudin-4 expression in End1/E6E7 cells. However, MPA unlike NET acted synergistically via the GR with TNF or LPS to upregulate C-C motif chemokine ligand (CCL)20 expression in End1/E6E7 cells. This was not an isolated event as MPA was also found to enhance TNF-induced expression of TNF receptor 2 (TNFRSF1B). The occurred against the backdrop of MPA but not NET repressing TNF-induced expression of IL6, IL1β and CCL5. In ectocervical tissues, MPA like NET did not regulate basal claudin-4 expression, but unlike NET downregulated desmoglein-1 expression. This suggest that MPA may increase the permeability of the endocervix and ectocervix via different mechanisms. This study was unable to established whether MPA and TNF synergistically upregulate CCL20 in ectocervical tissues. In PBMCs, however, MPA selectively enhanced LPS-induced expression of CCL20, but suppressed LPS-induced expression of IL6, IL8, IL1β and CCL5. Finally, MPA unlike NET was found to act alone or additively with TNF or LPS to increase HIV-1 replication in TZM-bl cells. While this suggest MPA directly affects HIV-1 replication, it was observed that the effects may also be indirect as secretions from PBMCs cotreated with MPA and LPS but not NET and LPS enhanced HIV-1 replication in TZM-bl cells. Taken together, the results shown in this study provides new insight into plausible mechanisms by MPA but not NET acting via the GR may enhance the susceptibility of the endocervix to HIV-1. Firstly, they suggest that MPA unlike NET may increase the permeability of the endocervix via a mechanism that is different from the ectocervix. Secondly, they suggest that the upregulation of select immune mediators and innate immune receptors by MPA but not NET in the endocervix in the absence of immune activation may render the endocervix vulnerable to HIV-1 infection. Thirdly, that MPA unlike NET is more likely to synergise with immune activators to further upregulate the expression of select immune function, but not tight junction genes in the endocervix. Collectively, this suggest MPA unlike NET can cooperate with GTIs to further increase the risk of HIV-1 acquisition in women residing in high risk regions. In this setting, NET-EN but not DMPA-IM would be a safer choice of injectable progestin-only contraceptive.